Second-generation governance indicators - Knack, Stephen; Manning, Nick; Kulger, Mark (2003)
This article summarizes progress made in a World Bank initiative funded by the UK Department for International Development to test and develop policy-relevant, politically acceptable, quantitative indicators of governance. There are two major principles involved in the process of generating indicators that are useful for practical reforms. Political acceptability is key in developing neutral quantitative benchmarks of good governance that can be embraced by reformers. Measures should also be institutionally specific so that reformers know which institutions to reform and how to do so. This article explores some of the most promising second-generation indicators of good governance and elaborates on how they are being used in World Bank operations. - Reproduced.
Keywords: Public administration; Good governance